Tsumoite and associated tellurides from the Au deposit Libcice near Novy Knin, Czech Republic: mineralogy and genetic significance - Sejkora,J.; Litochleb,J.; Plasil,J.; Bures,B. (Journal of Geosciences, 2009)
A mineral association with dominant pyrrhotite, tsumoite and gold, accompanied by minor tetradymite and pilsenite, has been found in material from the main vein of the abandoned Au deposit Libcice near Novy Knin, 25 km SSW of Prague, central Bohemia, Czech Republic. Tsumoite forms abundant silvery-grey tabular aggregates up to 1-4 mm in size. The mineral is grey-white to very weakly beige-coloured in reflected light, anisotropic, with VHN microhardness 68 (63-76) kg/mm2, with KVH = 1.21. Chemical analyses (electron microprobe) of matrix tsumoite yield Pb = 0.27, Cd = 0.12, Bi = 61.12, Te = 37.97, S = 0.01 and total of 99.50 wt. %, which corresponds to an empirical formula of Bi0.99Te1.00 based on 2 apfu. The chemical composition of Bi-rich schlieren-like domains within the tsumoite is Pb 0.20, Cd 0.09, Bi 63.06, Te 36.44, S 0.01, total 99.80 wt. %, and corresponds to empirical formula Bi1.02Te0.97 on the basis of 2 apfu. Both compositional varieties of tsumoite exhibit relatively small non-stoichiometry in Bi:Te ratio with respect to the ideal formula. The observed compositional range of tsumoite from Libcice corresponds to data published for this mineral species. Tsumoite is trigonal with space group P-3m1 and unit-cell parameters a 4.4204(9)-4.4210(8), c 24.043(7)-24.055(6) Å, V 406.9(1)-407.2(1) Å3. Pilsenite forms rare cleavable aggregates up to 80 μm. Its chemical composition Pb 0.09, Cd 0.12, Bi 67.63, Te 31.46, total 99.30 wt. % yields the empirical formula (Bi3.96Cd0.01Pb0.01)Σ3.98Te3.02 (based on 7 apfu). Younger tetradymite occurs in tiny irregular aggregates which partly overgrew and replaced tsumoite in association with native gold along fractures. The chemical composition of the tetradymite - Pb = 0.04, Cd = 0.11 Bi = 59.07, Te = 36.08, S = 4.50, total = 99.78 wt. % - corresponds to an empirical formula (Bi2.00Cd0.01)Σ2.01Te2.00S0.99 (based on 5 apfu). Associated pyrrhotite yielded formula Fe1-xS with x values in the range 0.13-0.14. Gold contains low Ag (up to 4 wt. %) and Hg (up to 1 wt. %). The studied mineral association formed at elevated temperatures (>300° C), probably in the course of two stages differing in bismuth activity, as well as fS2 and fTe2 values. Alternatively, the two stages could have reflected variation of hydrothermal and metamorphic process in space and time.
Keywords: Bismuth-tellurides; tsumoite; X-ray powder diffraction data; chemical composition; Libcice gold deposit; Czech Republic